2018
DOI: 10.1126/scisignal.aan8784
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes of AMPA responses in human induced pluripotent stem cell–derived neural progenitors in fragile X syndrome

Abstract: Altered neuronal network formation and function involving dysregulated excitatory and inhibitory circuits are associated with fragile X syndrome (FXS). We examined functional maturation of the excitatory transmission system in FXS by investigating the response of FXS patient-derived neural progenitor cells to the glutamate analog (AMPA). Neural progenitors derived from induced pluripotent stem cell (iPSC) lines generated from boys with FXS had augmented intracellular Ca responses to AMPA and kainate that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 83 publications
5
52
1
Order By: Relevance
“…Lending credence to this, previous studies have reported that differentially expressed genes in the blood of subjects with ASD are enriched for regulatory targets of CHD8 18 and FMR1 22 , two well-known rASD genes. Similarly, both lymphoblastoid cells of subjects with ASD and hiPSC-derived models of fragile-X syndrome show over-expression of mir-181 with a potential role in the disorder 23 . Likewise, leukocytes from toddlers with ASD show perturbations in biological processes such as cell proliferation, differentiation, and microtubules [24][25][26][27] , and these coincide with dysregulated processes seen in hiPSC-derived neural progenitors and neurons from individuals with ASD and brain enlargement 28,29 .…”
Section: Introductionmentioning
confidence: 98%
“…Lending credence to this, previous studies have reported that differentially expressed genes in the blood of subjects with ASD are enriched for regulatory targets of CHD8 18 and FMR1 22 , two well-known rASD genes. Similarly, both lymphoblastoid cells of subjects with ASD and hiPSC-derived models of fragile-X syndrome show over-expression of mir-181 with a potential role in the disorder 23 . Likewise, leukocytes from toddlers with ASD show perturbations in biological processes such as cell proliferation, differentiation, and microtubules [24][25][26][27] , and these coincide with dysregulated processes seen in hiPSC-derived neural progenitors and neurons from individuals with ASD and brain enlargement 28,29 .…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, we have previously observed decreased GluA2 expression following neonatal hypoxic seizures in wild type (WT) rats, which contributes to social interaction deficits, elevated activity-dependent Ca 2ϩ influx, altered downstream signaling, and increased epileptogenesis (Sanchez et al, 2001;Rakhade et al, 2008;Lippman-Bell et al, 2013Rosenberg et al, 2018). Finally, altered GluA2 subunit expression has been observed in several neurodevelopmental disorders, such as Rett syndrome, Fragile X syndrome, tuberous sclerosis, and RAB39B-associated mental retardation (Talos et al, 2008;Mignogna et al, 2015;Li et al, 2016;Achuta et al, 2018), pointing to a critical role of GluA2 in disease pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the search for FMRP-interacting proteins has resulted into the identification of dozens of partners, including ion channels (Bardoni et al, 2006 ; Ferron, 2016 ; and this study). Consistently with these findings, ion homeostasis defects in FXS neurons have been described (Chen et al, 2003 ; Meredith et al, 2007 ; Brown et al, 2010 ; Deng et al, 2013 ; Ferron et al, 2014 ; Hebert et al, 2014 ; Zhang et al, 2014 ; Contractor et al, 2015 ; Myrick et al, 2015 ; Wahlstrom-Helgren and Klyachko, 2015 ; Achuta et al, 2018 ). In particular, FMRP has been reported to directly interact with two members of the Voltage Gated Calcium Channels (VGCC) family, namely Ca v 2.1 and Ca v 2.2 (Ferron et al, 2014 ).…”
Section: Introductionmentioning
confidence: 57%